Physical Evaluation of Chlorpheniramine Maleate Wet Granulation - Adjie Wahyu Pradana; Putri Liana Dewi; Riska Septia Indriana (Strada Journal of Pharmacy, 2021)
Allergy is commonly happened in society, anti-histamine such as Chlorpheniramine Maleate (CTM) are fairly used to treat allergy. Granulation on CTM formulation plays major impact of mass produced of CTM tablets. Evaluation of granule formulation is conducted by observing flowability, moisture contents (MC), and angle of repose of granule. Flowability of granule is essential when compression phase of tablet. The result is moisture content is highly related with flowability, higher moisture content will reduce the flowability of granule. Hygroscopic material will more likely increased the MC and reduced the flowability. Leaner Angle of repose indicated rough surface of granule nucleation, which also related with flowability of granule.